Trends in local electricity market design: Regulatory barriers and the role of grid tariffs. (15th July 2022) - Maldet, Matthias; Revheim, Frida Huglen; Schwabeneder, Daniel; Lettner, Georg; del Granado, Pedro Crespo; Saif, Aziz; Löschenbrand, Markus; Khadem, Shafi
Abstract: New concepts of local electricity markets (LEMs) have led increased focus on the decentralization of energy systems and a raise in local energy communities (LECs). Under the right market-regulatory incentives, peer-to-peer (P2P) electricity trading schemes facilitate direct trade among the prosumers and enable active consumers of energy to share the self-generated electricity and make effective use of flexibility services provided by distributed energy resources (DERs). The paper presents a review of the state of implementation of LEMs and P2P. The research questions are: What grid tariff designs affect the value of peer-to-peer? How does a local energy market benefit from grid tariff designs? To address these questions, the authors survey the latest regulatory frameworks in Europe, focusing especially on Austria, Ireland, and Norway. Graphical abstract: Highlights: Local electricity markets applying peer-to-peer can promote decentral generation. Distribution system operator cooperation is mandatory for peer-to-peer trading. Regulatory peer-to-peer trading frameworks differ in European countries. Innovative grid tariffs are introduced. Innovative grid tariff design can promote peer-to-peer trading.